1997
DOI: 10.1002/bjs.1800840925
|View full text |Cite
|
Sign up to set email alerts
|

Electrically stimulated smooth muscle neosphincter

Abstract: An electrically stimulated smooth muscle neosphincter is feasible. It has potential applications in the management of faecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…this property of smooth muscle may be of potential advantage in anal sphincter reconstruction. 9 We have shown that the antropylorus, a smooth muscle segment, when surgically removed from gastroduodenal continuity and transposed to the perineum, provides a continuous tone and functions as an effective anal sphincter. [12][13][14] We have also reported that patients in whom the anorectum was excised (as in an aPR operation) functionally do not fare as well as patients in whom the native anal sphincter was preserved (traumatic anal sphincter damage) after the aPV transposition procedure, primarily because of inadequate voluntary control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…this property of smooth muscle may be of potential advantage in anal sphincter reconstruction. 9 We have shown that the antropylorus, a smooth muscle segment, when surgically removed from gastroduodenal continuity and transposed to the perineum, provides a continuous tone and functions as an effective anal sphincter. [12][13][14] We have also reported that patients in whom the anorectum was excised (as in an aPR operation) functionally do not fare as well as patients in whom the native anal sphincter was preserved (traumatic anal sphincter damage) after the aPV transposition procedure, primarily because of inadequate voluntary control.…”
Section: Discussionmentioning
confidence: 99%
“…3 in contrast, a smooth muscle being fatigue-resilient provides persistent tonic contraction, providing a potential benefit for anal reconstruction. [9][10][11] We have recently reported the technical feasibility and initial outcomes of perineal transposition of antropyloric valve (aPV), a smooth muscle segment, for neoanal reconstruction. [12][13][14] subsequent technical modification involving pudendal innervation of this transposed segment had also been attempted to improve neoanal sensation and provide neural control, although without much difference in outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation at frequencies of up to 10 Hz exhibit long semiperiods (longer than 50 ms) and long periods of depolarization that cause electrochemical and electrothermal tissue damage around the SEs before invoking phasic contractions [16]. Stimuli of frequencies higher than 100 Hz (stimulation semiperiod of 5 ms or smaller) need to be of larger than 10 V magnitude in order to produce contractions of the same strength (see equation (16)).…”
Section: Discussionmentioning
confidence: 99%
“…However, direct colonic stimulation is subject to additional constrains related to electrochemical phenomena hampering practical application of simple DC stimulation, since the DC currents in the tissue may cause electrochemical damage in the vicinity of the SEs by building up unbalanced ionic concentrations [13]. Experimental data con rm whitening of gastric tissue, bubbling or visible burns occurring prior to invoking contractions during stimulation with constant or low-frequency voltage applied across the SEs [16].…”
Section: Parametric Modelling Of Colonic Electrical Stimulation In Vivomentioning
confidence: 98%